Detection of Quantitative Trait Loci for Seed Size Traits in Soybean (Glycine max L.) - Dargahi, Hamidreza; Tanya, Patcharin; Srinives, Peerasak (Agriculture and Natural Resources, 2015)
Detection of validated and confirmed quantitative trait loci (QTLs) is essential to conduct more successful marker-assisted selection breeding programs. The objectives of this study were to determine the QTLs controlling seed size traits in soybean (Glycine max L.) and to compare those identified with the previously reported QTLs. One hundred thirty-five F2:3 lines derived from the cross MJ0004-6 × R18500 were evaluated in the experimental fields of Kasetsart University, Kamphaeng Saen, Nakhon Pathom, Thailand in a randomized complete block design with two replications each in the 2011 and 2012 growing seasons. The population was genotyped by 149 polymorphic simple sequence repeat markers and the genetic map consisted of 129 simple sequence repeat loci which converged into 38 linkage groups covering 1156 cM of soybean genome. There were 16 quantitative trait loci (QTLs) significantly associated with seed size traits across two seasons with single QTLs explaining between 7.4% and 18.4% of the phenotypic variation. One novel QTL (SL6) on linkage group K was consistently mapped in both seasons. Most QTLs were environment-sensitive, revealing that the genotype × environment interaction played an important role in expression of seed size traits in soybean. The majority of QTLs detected in the research were consistent with earlier QTLs reported by previous researchers.